The Trust Receipt and the Problem of Recordation or Notice Filing - Harold M. Carter (Washington University Law Quarterly, 1951)
The trust receipt as a security device originated in connection with purchases by importers from foreign manufacturers; however, it may be used as well in financing domestic transactions, and today it has become well entrenched in the domestic business world of the United States. The first extensive domestic use of this security device was by the automobile industry. From the automobile industry the trust receipt has now spread to many other articles sold to consumers on the installment plan, such as radios, refrigerators, washing machines, etc. Since the date in 1876 when the first case to use the term “trust receipt” was decided, this security device has been a so-called “hot potato” for the judiciary. There has been great conflict and confusion as to what to do with the trust receipt whether to recognize it as a security device sui generis, or whether to classify it as one of the existing well-entrenched security instruments. Probably the basic reason for this conflict has been the secret lien aspect of the trust receipt, and the court's reluctance to give recognition to any device which would inflict a secret lien of any description upon the business world and the general public. This secret lien aspect of the trust receipt seemed to create an insurmountable obstacle in the field of security transactions. However, beginning with the Uniform Trust Receipts Act of 1933 great progress has been made to clarify the status of the trust receipt and to overcome the conflict as to recordation or notice filing. Further progress may be expected as a result of the work being done on the proposed Uniform Commercial Code.
Keywords: Trust receipts